A state space MPC with extensions to multi-rate control - Wang, Yuxin (Nanyang Technological University, 2021)
In industrial systems and practical applications, the application of multi-rate systems has become more and more extensive. How to better perform multi-rate control is a very important topic. This dissertation focuses on the control method of MPC extension to multi-rate systems. First the advantages of MPC control method compared to traditional methods and what is multi-rate control are introduced. The advantages of MPC method for multi-rate control is also illustrates. Then, optimal state feedback law and the state estimator is derived based on SISO state-space model. On the basis of it, MRIC and MROC can use the same way to be determined. For test and experimental part, a simple example was used to realize the simulation in MATLAB, and the verification of the feasibility of the algorithm was completed. In the experimental part, a simple example was used to realize the simulation in MATLAB, and the verification of the feasibility of the algorithm was completed. The disturbance situation is also discussed, and the results show that the system has relatively good robustness. At last, this dissertation is summarized and some methods and prospects for improvement are put forward.